The Impacts of Canva Media for the Continual Advancement of Indonesian EFL Learners’ Writing Proficiency Levels - Wijaya, Kristian Florensio (English Education Department, 2024)
Abstract Second language educators in this modern age are granted with limitless digital learning platforms to be further integrated into their habitual writing classroom activities. For this reason, they need to embrace this learning aspiration by constantly internalizing a wide variety of technological tools promoting holistic educational rewards among EFL learners. This small-scale library study aimed to investigate the impacts of Canva media on the continual advancement of Indonesian EFL learners’ writing proficiency levels. To achieve this major study objective, the researcher plotted a thematic analysis while analyzing some relevant findings from 30 previous Canva media and writing scientific articles forming in varied reputable national journal article platforms. A thematic analysis was useful in yielding more accurate research results since the researcher obtained more nuanced insights concerning the research areas that were specifically investigated. Based on the thematic analysis, the researcher deduced that Canva media was beneficial in supporting Indonesian EFL learners in making smoother writing transitions among the shared ideas and gradually shifting them into more ingenious writers. Keywords: Digital media; Canva; EFL learners; library study; thematic analysis.